Prolonged QTc Interval in Diabetes Mellitus: Frequency and Correlation with Glycemic Control - Marrium; Shabbir, Muhammad Araib; Jamshaid, Kainat; Danish, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Prolonged QTc interval is a known predictor of ventricular arrhythmias and sudden cardiac death. Diabetic patients are at increased risk of QTc prolongation due to underlying autonomic neuropathy and metabolic disturbances. Identifying its frequency and correlation with glycemic control can aid in early detection and prevention of cardiac complications. Objective: To determine the frequency of prolonged QTc interval in diabetic patients attending follow-up at the Outpatient Department of Medicine, and to compare mean HbA1c levels between patients with and without QTc prolongation. Material and Methods: A cross-sectional analysis was conducted at Department of Medicine, Jinnah Hospital, Lahore, from January to June 2023, involving 362 adult patients with type 2 diabetes mellitus attending follow-up appointments. Demographic and clinical data including age, sex, body mass index (BMI), duration of disease, and HbA1c levels were recorded. Each participant underwent a 12-lead electrocardiogram (ECG) to determine QTc interval, which was corrected for heart rate using Bazett’s formula. Prolongation was defined as QTc ≥450 ms in males and ≥470 ms in females. Statistical evaluation was performed using SPSS version 25, applying chi-square and independent t-tests, with a significance threshold set at p < 0.05. Results: Prolonged QTc was observed in 112 (30.9%) patients. Although not statistically significant, a higher frequency of QTc prolongation was seen in females and those with uncontrolled diabetes. Mean HbA1c was higher in patients with prolonged QTc (8.17 ± 1.39%) than those with normal QTc (7.89 ± 1.41%) (p = 0.087). Conclusion: QTc prolongation is common in diabetic patients, particularly in those with poor glycemic control. Routine ECG monitoring is advisable for early risk identification.